Low-Dose Lithium Stabilizes Human Endothelial Barrier by Decreasing MLC Phosphorylation and Universally Augments Cholinergic Vasorelaxation Capacity in a Direct Manner - Bosche, Bert; Molcanyi, Marek; Rej, Soham; Doeppner, Thorsten R.; Obermann, Mark; Müller, Daniel J.; Das, Anupam; Hescheler, Jürgen; Macdonald, R. Loch; Noll, Thomas; Härtel, Frauke V. (Frontiers in Physiology, 2016)
Lithium at plasma concentrations up to 1 mmol/L has been used in patients suffering from bipolar disorder for decades and has recently been shown to reduce the risk for ischemic stroke in these patients. The risk for stroke and thromboembolism depend not only on cerebral but also on general endothelial function and health; the entire endothelium as an organ is therefore pathophysiologically relevant. Regardless, the knowledge about the direct impact of lithium on endothelial function remains poor. We conducted an experimental study using lithium as pharmacologic pretreatment for murine, porcine and human vascular endothelium. We predominantly investigated endothelial vasorelaxation capacities in addition to human basal and dynamic (thrombin-/PAR-1 receptor agonist-impaired) barrier functioning including myosin light chain phosphorylation (MLC-P). Low-dose therapeutic lithium concentrations (0.4 mmol/L) significantly augment the cholinergic endothelium-dependent vasorelaxation capacities of cerebral and thoracic arteries, independently of central and autonomic nerve system influences. Similar concentrations of lithium (0.2-0.4 mmol/L) significantly stabilized the dynamic thrombin-induced and PAR-1 receptor agonist-induced permeability of human endothelium, while even the basal permeability appeared to be stabilized. The lithium-attenuated dynamic permeability was mediated by a reduced endothelial MLC-P known to be followed by a lessening of endothelial cell contraction and paracellular gap formation. The well-known lithium-associated inhibition of inositol monophosphatase/glycogen synthase kinase-3-β signaling-pathways involving intracellular calcium concentrations in neurons seems to similarly occur in endothelial cells, too, but with different down-stream effects such as MLC-P reduction. This is the first study discovering low-dose lithium as a drug directly stabilizing human endothelium and ubiquitously augmenting cholinergic endothelium-mediated vasorelaxation. Our findings have translational and potentially clinical impact on cardiovascular and cerebrovascular disease associated with inflammation explaining why lithium can reduce, e.g. the risk for stroke. However, further clinical studies are warranted.